2022
DOI: 10.1177/1071181322661456
|View full text |Cite
|
Sign up to set email alerts
|

Effects of semi-automatic pistol slide pull device on law-enforcement racking process

Abstract: Under life-threatening circumstances, the interaction between law enforcement officers and pistol slides during the racking and reloading process is critical to survival. Nine expert law-enforcement officers were recruited to investigate the effects of slide pull devices on application time and performance using semi-automatic pistols. Participants were asked to manually rack both standard and augmented slide pull devices and then clean three magazines. Videos and times were recorded to compare the slide types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Further research is needed to determine which and what number of accessories are best suited for improving the public’s perception. Further research can also be done to see how standards compare to real experience, as studies into that interaction in the past have found that occasionally standards are excessive when compared to what people do on their own (Stone et al 2022). As appropriately asked by Johnson et al, 2014: “officers apparently need to wear some sort of uniform for citizen recognition, so where is the line drawn regarding which accessories are necessary and which are not?”…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research is needed to determine which and what number of accessories are best suited for improving the public’s perception. Further research can also be done to see how standards compare to real experience, as studies into that interaction in the past have found that occasionally standards are excessive when compared to what people do on their own (Stone et al 2022). As appropriately asked by Johnson et al, 2014: “officers apparently need to wear some sort of uniform for citizen recognition, so where is the line drawn regarding which accessories are necessary and which are not?”…”
Section: Discussionmentioning
confidence: 99%
“…Garnering an overly- militarized image may diminish an officer’s or a department’s ability to effectively carry out this commitment (Quill, 2016). Different designs and variants of equipment, such as firearm slide augments, can also directly impact an officer’s error rate (Stone et al, 2022). If an agency uniforms its officers in a more militarized way, previous research indicates that this evokes negative feelings from citizens (Blaskovits et al, 2021; Cooke, 2004).…”
Section: Introductionmentioning
confidence: 99%